The current state of forensic imaging– clinical forensic imaging - Fabrice, Dedouit; Mathilde, Ducloyer; Jamie, Elifritz; Natalie, L. Adolphi; Grace Yi-Li, Wong; Summer, Decker; Jonathan, Ford; Yanko, Kolev; Michael, Thali (Springer Nature, 2025)
Clinical forensic imaging could be de ned as the use of imaging rst realised for medical care as evidence for a judicial purpose. It requires both forensic experts and clinical radiologists to have a good understanding of imaging modalities and indications and a solid knowledge of the correct terminology. This second part of the review describes the main situations in which imaging may be used for forensic purposes, i.e. blunt trauma, penetrating injuries, asphyxia, physical abuse and neglect.